The changes of peroxide number of coconut meal during storage and fermentation processed with Aspergillus nige - Helmi Hamid; T Purwadaria; T Haryati; A.P Ketaren (Jurnal Ilmu Ternak dan Veteriner, 1999)
The effect of fermentation process and duration of storage of fermented coconut meal with Aspergillus niger on its peroxide number has been studied. First stage of experiment was arranged in a completely randomized design with four treatments (raw coconut meal, 0 and 4 day aerobic fermentation incubation and after 2 day anaerobic enzymatic incubation). The peroxide number was determined as potentiality for rancidity. The three incubation processes decreased the peroxide number significantly. The highest reduction was obtained at 4 day aerobic fermentation (49.7%). The decrease of peroxide number of fermented coconut meal was correlated with the decrease of lipid content. The regression coefficient is highly significant (r2 = 0.76, P<0.01). In the second experiment, the effect of storage on the peroxide number of fermented product was conducted by factorial design 2x3x4 i.e., two type of substrates (fermented and non fermented coconut meal), 3 storage temperatures (-13, 4, and 29oC) and 4 storage times (1, 2, 3, and 4 months). Statistical analysis for lipid contents showed that there was significant interaction (P<0.05) between kind of substrates and storage time. The lipid content of fermented product was decreasing from the first up to the third month of storage, then it was increasing at the fourth month, but the lipid content of non fermented coconut meal did not significantly changed (P>0.05). Statistical analysis for the peroxide number showed that there was highly significant interaction between the type of substrates and storage temperature. The peroxide number on the fermented products did not significantly increase, where as the non fermented products show significantly increased during storage course. The significant interaction between storage duration and temperature observed. At low temperatures (-13 and 4°C) storage the peroxide number increased 44%, while at high temperature (29°C) up to 95%. The highest peroxide number on the fermented product (43.5 ppm) was obtained at the temperature storage of 29°C for 4 month period. This value is still under rancidity limit (80 ppm). It could be concluded that fermentation process reduced the rancidity of coconut meal.   Key words : Coconut meal, fermentation, peroxide number, Aspergillus niger